Marcadores moleculares na identificação de corridas de homozigose e endogamia nas raças curraleiro pé-duro e pantaneiro - Santos, Marcelo Fernandes dos (2021)
The runs of homozygosity (ROHs) can be used to estimate more accurate population parameters and genomic regions under selection in different species and breeds. Therefore, this approach can be used in locally adapted breeds to identify genes of economic interest and estimate autozygosity, enabling the optimization of selection and mating strategies and mitigating their extinction risk. The objective of this work is to identify and characterize the ROHs present in locally adapted breeds Curraleiro Pé-Duro (CPD) and Pantaneiro (PANT) in order to identify genes under selection and estimate their inbreeding coefficient (FROH). The ROHs were identified in 126 and 35 animals of the CPD and PANT breeds, respectively, with data from 54,000 SNP markers. For the identification of ROHs, the following criteria were used: a) sliding window of 50 SNPs, b) minimum number of 100 consecutive SNPs in each ROH, c) minimum length of 1 Mb, c) maximum interval between homozygous consecutive SNPs of 0, 5 Mb, d) maximum of five SNPs with absent genotypes, 1083 and 140 ROHs were found in the CPD and PANT breeds, respectively, and that the predominant pattern of ROHs in the studied breeds are those of medium to long size, which demonstrates recent events of autozygosity. Six islands of homozygosity were identified in both breeds on autosomal chromosomes 6, 8, 10, 13, 14 and 17. Genes and QTLs previously related to traits of interest are located in the segments found, highlighting QTLs associated with production and quality traits of milk (57%), as those involved in the content of proteins such as caseins and genes associated with the immune system, such as the genes of the beta defensin family. The estimated inbreeding coefficient showed that both breeds have low autozygosity (2-4%), which differs from what is expected for populations with a reduced genetic base such as those studied. The present work identified six homozygous islands in common in the Curraleiro Pé-Duro and Pantaneiro breeds, located in genomic regions previously reported to be associated with characteristics of economic interest, such as disease resistance and milk protein content, which can be considered candidate regions the selection. The inbreeding coefficient estimated based on the ROHs showed that inbreeding is low (2 to 4%) in the studied populations, diverging from what was expected in small populations.